2021
DOI: 10.1051/0004-6361/202140371
|View full text |Cite
|
Sign up to set email alerts
|

A bright inner disk and structures in the transition disk around the very low-mass star CIDA 1

Abstract: The frequency of Earth-sized planets in habitable zones appears to be higher around M-dwarfs, making these systems exciting laboratories to investigate planet formation. Observations of protoplanetary disks around very low-mass stars and brown dwarfs remain challenging and little is known about their properties. The disk around CIDA 1 (~0.1–0.2 M⊙) is one of the very few known disks that host a large cavity (20 au radius in size) around a very low-mass star. We present new ALMA observations at Band 7 (0.9 mm) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 80 publications
2
54
3
Order By: Relevance
“…As in Section 5, we used an X-ray luminosity of L x = 10 31 ergs −1 , α dz = 10 −4 , and r dz = 10 AU, but we take the snapshot at 1.2 Myr, since the gap opens earlier when using the initial condition from Equation A.1. The main difference is that now the surface brightness of the inner disk is comparable to that of the outer ring in the millimeter continuum, as observed in some transition disks (Hendler et al 2018;Pinilla et al 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As in Section 5, we used an X-ray luminosity of L x = 10 31 ergs −1 , α dz = 10 −4 , and r dz = 10 AU, but we take the snapshot at 1.2 Myr, since the gap opens earlier when using the initial condition from Equation A.1. The main difference is that now the surface brightness of the inner disk is comparable to that of the outer ring in the millimeter continuum, as observed in some transition disks (Hendler et al 2018;Pinilla et al 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Through radiative transfer models, it has been possible to measure the radial extent of the dust cavity for a wide sample of transition disks (van der Marel et al 2016b), and observations at different wavelengths have also shown that some of these objects retain a compact dust component close to the star (e.g. Espaillat et al 2010;Benisty et al 2010;Olofsson et al 2013;Matter et al 2016;Kluska et al 2018;Pinilla et al 2019Pinilla et al , 2021, demonstrating that for some transition disks the gap is not completely devoid of dust.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Rigliaco et al (2012) and others (e.g., Alcalá et al 2017) have shown that the combination of accretion luminosity measured with a significant number of emission lines ( 5-6) leads to estimates of accretion luminosity with small uncertainties (∼0.2-0.3 dex) and good agreement with the values obtained from the fit of the Balmer continuum. Comparing accretion luminosity determinations from lines at different wavelengths also provides a way to independently determine extinction (e.g., Pinilla et al 2021). However, it should be noted that only a proper inclusion of the impact of extinction and of veiling due to accretion at all stages of the spectral analysis overcomes the degeneracies between these parameters, and that the UV-excess is key for determining the excess due to accretion (e.g., Manara et al 2013a;Herczeg and Hillenbrand 2014).…”
Section: Spectral Types Stellar and Accretion Luminositymentioning
confidence: 99%
“…1. ALMA observation in Band 7 (0.9 mm) of the system CIDA 1 (Pinilla et al 2021), with a beam size of 0.050 × 0.034 (FWHM) indicated by the white ellipse in the bottom left corner.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we aim to reproduce the observed dust and gas emission of the disk, to evaluate whether the presence of the observed substructures can be explained by the interactions of the disk with an embedded planet. While Pinilla et al (2021) assume an analytical gap shape, we obtain it from hydrodynamical simulations. We employ full 3D modeling to take into account the dynamical and radiative aspects of the disk, along with the effects introduced by interferometric observations with ALMA.…”
Section: Introductionmentioning
confidence: 99%